High School Student-Athletes: Their Motivation, Study Habits, Self-Discipline, Academic Support, and Academic Performance - Dian Pujianto; Yahya Eko Nopiyanto; Cahyo Wibowo; Ipa Sari Kardi; Septian Raibowo; Bayu Insanistyo; Ibrahim; Baharuddin Hasan; Agus Sutriawan (Physical Education Theory and Methodology, 2024)
Study purpose. Student-athletes have a role that is not easy to balance between the role of being an athlete and the role of being a student at school. Not a few of them have obstacles in balancing both roles. This study aims to reveal the characteristics of secondary school student-athletes in Bengkulu City. The main objectives are to describe the level of achievement motivation, study habits, self-discipline, academic support, and academic performance.